Accelerated atherosclerosis in patients with chronic inflammatory rheumatologic conditions. (October 2015) - Hong, Jison; Maron, David J; Shirai, Tsuyoshi; Weyand, Cornelia M
Atherosclerosis is a complex inflammatory disease involving aberrant immune and tissue healing responses, which begins with endothelial dysfunction and ends with plaque development, instability and rupture. The increased risk for coronary artery disease in patients with rheumatologic diseases highlights how aberrancy in the innate and adaptive immune system may be central to development of both disease states and that atherosclerosis may be on a spectrum of immune-mediated conditions. Recognition of the tight association between chronic inflammatory disease and complications of atherosclerosis will impact the understanding of underlying pathogenic mechanisms and change diagnostic and therapeutic approaches in patients with rheumatologic syndromes as well as patients with coronary artery disease. In this review, we provide a summary of the role of the immune system in atherosclerosis, discuss the proposed mechanisms of accelerated atherosclerosis seen in association with rheumatologic diseases, evaluate the effect of immunosuppression on atherosclerosis and provide updates on available risk assessment tools, biomarkers and imaging modalities.